2011
DOI: 10.1164/rccm.201010-1685pp
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Idiopathic Pulmonary Neuroendocrine Cell Hyperplasia

Abstract: Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) is being recognized with increasing frequency. Diagnostic and treatment information is limited. A systematic review is presented, focusing on patient demographics, clinical presentation, diagnosis, treatment options, and outcomes. A systematic electronic literature search was conducted for adult DIPNECH cases reported in the English literature during the past 6 years. Twenty-four DIPNECH cases were identified. Another case from our institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
167
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(181 citation statements)
references
References 34 publications
5
167
2
7
Order By: Relevance
“…His CT of chest finding revealed emphysema, ground-glass opacities, multiple lung cysts, septal thickening, and subpleural honeycombing, which have all been reported to be associated with SFTPC mutations. In addition, there was some evidence of air-trapping and mosaic attenuation, which are well-described radiographic findings in DIPNECH [23,33].…”
Section: Discussionsupporting
confidence: 58%
“…His CT of chest finding revealed emphysema, ground-glass opacities, multiple lung cysts, septal thickening, and subpleural honeycombing, which have all been reported to be associated with SFTPC mutations. In addition, there was some evidence of air-trapping and mosaic attenuation, which are well-described radiographic findings in DIPNECH [23,33].…”
Section: Discussionsupporting
confidence: 58%
“…The presence of diffuse proliferation of PNEC without the aforementioned risk factors is suggestive of DIPNECH. It is more prevalent in females (92%) with a mean age at presentation of 58 years [2]. Based on a review of literature by Nassar et al, the most common presenting symptoms reported are cough (71%), dyspnea (63%), and wheezing (25%) [2].…”
Section: Discussionmentioning
confidence: 99%
“…It is more prevalent in females (92%) with a mean age at presentation of 58 years [2]. Based on a review of literature by Nassar et al, the most common presenting symptoms reported are cough (71%), dyspnea (63%), and wheezing (25%) [2]. The most common finding www.pneumonologia.viamedica.pl on PFTs were an irreversible obstructive defect (54−78% of patients), however, mixed (17%), and restrictive pattern (13%) were also noted [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations